Internal auditors’ quality as a mediation variable in fraud prevention in the government of Jambi Province - Netty Herawaty; Haryadi Haryadi; Enggar Diah Puspa Arum; Sri Rahayu (Program Magister Ilmu Ekonomi Pascasarjana Universitas Jambi, 2021)
This study aims at examining and analyzing the effect of the government internal control system and the role of internal auditors directly and indirectly on fraud prevention through the quality of internal auditors. This study uses primary data obtained from questionnaires distributed to examiners in 11 districts/municipalities within the province and representatives of the Jambi Province Financial and Development Supervisory Agency. Sampling was carried out on the entire population, namely auditors with the functional auditor position, amounting to 272. The samples processed were 225 people. SEM-PLS has been employed as the main tool of analysis. The results showed that the government internal control system variable directly or indirectly affected fraud prevention. Meanwhile, the role of internal auditors does not directly affect fraud prevention. This variable affects fraud prevention through the mediating variable of the quality of the internal auditors as the quality of the internal auditors is said to be the full mediation.